Corneal Microneedles: Single Administration of a Biodegradable, Separable Microneedle Can Substitute for Repeated Application of Eyedrops in the Treatment of Infectious Keratitis (Adv. Healthcare Mater. 11/2021). Issue 11 (9th June 2021) - Park, SeungHyun; Lee, KangJu; Kang, Heekyoung; Lee, YeJin; Lee, JiYong; Kim, Jeong Hun; Song, Hyun Beom; Ryu, WonHyoung
Abstract : In article number 2002287 by WonHyoung Ryu, Hyun Beom Song, and co‐workers, a biodegradable and separable microneedle into the cornea is studied as a substitute for multiple eyedrops in the treatment of infectious keratitis. This study showcases the mechanical integrity and release optimization with three different formulations of drug‐tip and demonstrates that a single microneedle injection can be used instead of an initial three days of multiple eyedrops in vivo.